Decolonizing Palestinian political economy : de-development and beyond - Turner, Mandy; Shweiki, Omar (New York Palgrave Macmillan, 2015)
​"The volume brings together cutting-edge political economy analyses of the Palestinian people: those living in the occupied territory of the West Bank and Gaza Strip, those living within Israel, and refugees in Arab states. It is a must-read for those who wish to understand the historical origins and contemporary realities that face Palestinians" LC page.
Part I: De-developmentExplored 1. The economic strategies of occupation: confining development and buying-off peace / Sahar Taghdisi-Rad -- 2. The political economy of western aid in the occupied Palestinian Territory since 1993 / Mandy Turner -- 3. Hydro-apartheid and water access in Israel-Palestine: challenging the myths of cooperation and scarcity / Clemens Messerschmid -- 4. (En)gendering de-development in East Jerusalem: thinking through the 'everyday' / Nadera Shalhoub-Kerkovian and Rachel Busbridge -- part II 5. Palestinian refugees: from 'spoilers' to agents of development / Ingrid Jaradat Gassner -- 6. Impeded development: the political economy of the Palestinian Arabs inside Israel / Mtanes Shehadeh and Raja Khelidi -- 7. State-directed 'development' as a tool for dispossessing the indigenous Palestinian Bedouin-Arabs in the Naqab / Isamel Abu-Saad -- 8.Planning the divide: Israel's 2020 master plan and its impact on East Jerusalem / Rami Nasrallah -- part III 9. Neoliberalism and the contradictions of the Palestinian authority's state-building programme / Raja Khalidi and Sobhi Samour -- 10. The role of the tunnel economy in redeveloping Gaza / Nicolas Pelham -- 11. Before and beyond neoliberalism: the political economy of national liberation, the PLO and 'amal itima'i / Omar Shweiki -- 12. Learning the lessons of Oslo: state-building and freedoms in Palestine / Mushtaq H. Khan.
Includes bibliographical references and index
Keywords: Social Groups; PALESTINIANS; HISTORY; POLITICAL CONDITIONS; ECONOMIC CONDITIONS; GOVERNMENT POLICY